The Gambia: Recent developments in public agricultural research - Stads, Gert-Jan; Manneh, Faye (International Food Policy Research Institute, 2010)
The Gambia is one of Africa's smallest countries, so its agricultural research and development (R&D) capacity and investment levels are understandably low compared with most of its neighbors. The country's total agricultural R&D investment levels have been erratic over the past two decades due to significant fluctuations in government and donor funding. In 2008, The Gambia invested close to 20 billion dalasis or 2.6 million PPP dollars in agricultural R&D, both in 2005 prices. Unless otherwise stated, all dollar values in this note are based on purchasing power parity (PPP) exchange rates. PPPs reflect the purchasing power of currencies more effectively than do standard exchange rates because they compare the prices of a broader range of local—as opposed to internationally traded—goods and services. Agricultural R&D capacity levels in The Gambia have contracted somewhat since the turn of the millennium. In 2008, the country employed 38 full-time equivalent (FTE) research staff compared with 42 in 2000.